Pulmonary stenosis in complicated monochorionic twin pregnancies: prevalence, management and outcome. (4th August 2015) - Stagnati, V.; Chalouhi, G. E.; Essaoui, M.; Giuseppi, A.; Stirnemann, J. J.; Le Bidois, J.; Ville, Y.
Abstract: Objective: To review prevalence, management and prognostic factors of pulmonary stenosis (PS) in monochorionic diamniotic (MCDA) pregnancies complicated by twin‐to‐twin transfusion syndrome (TTTS). Methods: Retrospective study over the last 10 years in a single referral center. We reviewed fetal echocardiography data of all MC twin cases with diagnosis of isolated PS. We assessed fetoscopy characteristics of those that underwent laser coagulation. We collected data regarding perinatal outcome, neonatal echocardiography and cardiac management. Results: We found 24 cases of isolated PS among 2091 MCDA pregnancies. Among 1052 complicated MCDA that underwent fetal laser surgery, 22 (2.09%) developed PS of which 20 were diagnosed prenatally. Two cases were diagnosed in uncomplicated MCDA pregnancies (0.2%). Four of 22 (18.18%) cases with TTTS showed in utero regression after laser treatment. Thirteen newborns (65%) required valvular dilatation. Peak systolic velocities in the pulmonary artery trunk (PSV‐PA) at diagnosis and the interval between the diagnosis of TTTS and that of PS were significantly different ( p  < 0.001 and p  = 0.05 respectively) between PS requiring cardiac intervention and those who did not. Conclusion: An elevated PSV‐PA at the time of PS diagnosis and a short time‐interval between fetoscopic laser surgery and PS diagnosis are predictive of the need for interventional treatment after birth. © 2015 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Pulmonary stenosis/atresia is the most reported malformation in monochorionic twin pregnancies, more frequently in case of TTTS. Previous publications consisted of small case series not allowing taking clinical‐relevant conclusion. What does this study add? Mild increase in PSV‐PA has no significant clinical consequences and usually regresses after birth; an elevated PSV‐PA at the time of diagnosis and a short time‐interval between TTTS and PS seem to be associated with a higher risk of postnatal PS interventional treatment. Fetuses with significant PS should be referred to a pediatric cardiology unit for neonatal care including, in some cases, balloon dilatation of pulmonary valve.